Self-Representations of Cultural Identity in South African Indian Filmmaking, 2004 – 2017 - Prem, Temara (University of the Witwatersrand, Johannesburg, 2024)
In a post-apartheid context, the filmmaking practices of South African Indian diasporic communities serves as a fertile ground for examining complexities of cinematic representation of identity negotiations and cultural expression. This research interrogates the extent to which cinematic self-representation in three South African Indian films—Broken Promises (2004), For Better For Worse (2010), and Keeping Up with the Kandasamys (2017)—enables a visibility of complex heterogenous representations of cultural identity. Employing a combination of contextual and textual analysis, the study conducts a detailed critical analysis inspecting how these films navigate between cultural homogenisation and heterogeneous identity constructions and representations. The research finds that cultural specificity is exhibited in the films to limited degrees while more monolithic representations do serve to unify South African Indian experiences while also extending accessibility to external audiences. The extent to which these films manage to create visibility of the complex identities is intricately tied to varying modes of production and distribution, revealing both the opportunities and constraints in the ongoing project of cinematic self-representation for South African Indian communities. This study contributes to the underexamined field of South African Indian film scholarship, as well as broader discourses of postcolonial filmmaking by re- interpreting Bhabha's concept of the 'third space' (1994) as complicated by the specificities of 'place'. Emerging from the findings, an analytic framework of ‘Prismatic Analysis’ is conceptualised and proposed as a focused framework within postcolonial film studies that captures the complex and hybrid nature of postcolonial diasporic communities.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Humanities, Wits School of Art, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; South African Indians; Cultural Identity; Postcolonial Cinema; Post-Apartheid Cinema; Keeping Up with the Kandasamys; For Better For Worse; Broken Promises; Representation; Diaspora; Hybridity; Place; Political Economy; SDG-9: Industry, innovation and infrastructure